Tinjauan Pelaksanaan Sistem Penyimpanan Rekam Medis Berdasarkan Standar Akreditasi Di UPTD Puskesmas Kotanopan Mandailing Natal - Zulham Andi Ritonga; Hasran Ependi Lubis (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Storage of medical records is one of the assessments in puskesmas accreditation standards. The medical record file storage system is very important to do in health care institutions, because the storage system can make it easier for medical record files to be stored in storage racks, speed up the recovery or retrieval of medical record files stored on storage racks, easy to return, and protect record files. from theft, physical, chemical and biological damage. The purpose of this study was to determine how the implementation of a medical record storage system based on puskesmas accreditation standards, which was carried out in August 2020. The research method used was descriptive research with a qualitative approach. The number of research informants was 4 people. Storage of medical records had not used tracers and expedition book as a means of replacing medical record files and notes in and out of borrowed medical record files. Meanwhile, tracer and expedition books can assist officers in searching for missing / out of place medical record files. This can hamper the provision of patient medical record files that are needed. It is hoped that the UPTD Puskesmas Kotanopan will provide regular training or debriefing to medical record officers